2011
DOI: 10.1007/978-1-4419-6108-2_11
|View full text |Cite
|
Sign up to set email alerts
|

The Theory of the Lemon Markets in IS Research

Abstract: The "lemon" problem was initially posed by Nobel Prize winner Akerlof in his seminal article of 1970 and showed how a market with unbalanced information, called information asymmetry, can lead to complete disappearance or to offerings with poor quality where bad products (lemons) wipe out the good ones. Empirical evidence for Akerlof"s theory came originally from the market of used cars, where the lemon is a well known problem. However the theoretical model of the "lemon" problem has proven also to be valid on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Although trust has a reciprocal nature, it is the agent who has to work hardest on trust-building mechanisms in order to maintain or to increase the level of trust. Devos et al found that there is always incentive for adverse selection and moral hazard as long as the SME-principal is not willing to pay the costs required to avoid the asymmetry of information (Devos et al, 2010). The market where SMEs buy IT is attractive for small independent software vendors (ISV) acting as business partners of top-notch ERP suppliers and IS/IT suppliers.…”
Section: Discussionmentioning
confidence: 99%
“…Although trust has a reciprocal nature, it is the agent who has to work hardest on trust-building mechanisms in order to maintain or to increase the level of trust. Devos et al found that there is always incentive for adverse selection and moral hazard as long as the SME-principal is not willing to pay the costs required to avoid the asymmetry of information (Devos et al, 2010). The market where SMEs buy IT is attractive for small independent software vendors (ISV) acting as business partners of top-notch ERP suppliers and IS/IT suppliers.…”
Section: Discussionmentioning
confidence: 99%
“…Given the harmful effects of molecular deception, it is necessary to reduce information asymmetry, in order to promote cooperation between gene players, in the normal functioning of the genome. For instance, in the theory of incomplete contracts, a topic linked with the economics of information, reduction in information asymmetry reduces the likelihood of deception between parties, which consequently promotes trust (Devos et al, 2012) and so cooperation (Lorenz, 1999). Given this framework, one may suggest a form of “molecular trust” that is promoted when the information asymmetry between two gene players is reduced (effectively increasing transparency), with the effect of promoting utility (fitness) for both players, since deception is less likely to occur.…”
Section: Genesis Of Bio-molecular Interactionsmentioning
confidence: 99%
“…While most LMT research has been undertaken in the used car market [14], it has been applied to the study of other markets. Examples include the area of information systems [15] where e-markets, e-commerce, and e-auctions have been studied [16][17][18]. Given that it has been used in the realm of information systems before, LMT was considered a good fit for our study.…”
Section: Theoretical Lensmentioning
confidence: 99%